Comparison of embedded atom method potentials for small aluminium cluster simulations - Budi, A.; Henry, D.; Gale, Julian; Yarovsky, I. (IOP: Institute of Physics Publishing Ltd, 2009)
In this paper, we present a comparison of the performance of a series of embedded atom methodpotentials for the evaluation of bulk and small aluminium cluster geometries and relativeenergies, against benchmark density functional theory calculations. In general, the non-pairwisepotential-B (NP-B), which was parametrized against Al cluster data, performs the best.